2018
DOI: 10.1073/pnas.1813058115
|View full text |Cite
|
Sign up to set email alerts
|

Resistance protein Pit interacts with the GEF OsSPK1 to activate OsRac1 and trigger rice immunity

Abstract: Resistance (R) genes encode intracellular nucleotide-binding/leucine-rich repeat-containing (NLR) family proteins that serve as critical plant immune receptors to induce effector-triggered immunity (ETI). NLR proteins possess a tripartite domain architecture consisting of an N-terminal variable region, a central nucleotide-binding domain, and a C-terminal leucine-rich repeat. N-terminal coiled-coil (CC) or Toll-interleukin 1 receptor (TIR) domains of R proteins appear to serve as platforms to trigger immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 61 publications
2
58
0
Order By: Relevance
“…Next, we wondered whether PID3 recruits other component(s) in the signalling pathway. The CC domains of some NLR proteins are key for interactions with downstream signalling components (Shen et al ., ; Inoue et al ., ; Wang et al ., ); indeed, our experiments indicated that the CC domain‐deleted PID3 failed to convey blast resistance (data not shown). We therefore performed yeast two‐hybrid screening with PID3‐CC as bait.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Next, we wondered whether PID3 recruits other component(s) in the signalling pathway. The CC domains of some NLR proteins are key for interactions with downstream signalling components (Shen et al ., ; Inoue et al ., ; Wang et al ., ); indeed, our experiments indicated that the CC domain‐deleted PID3 failed to convey blast resistance (data not shown). We therefore performed yeast two‐hybrid screening with PID3‐CC as bait.…”
Section: Resultsmentioning
confidence: 66%
“…We therefore used OsRac1 RNAi kd plants rather than knockout plants. Similarly, an investigation of the function of OsSPK1 in OsRac1 activation (Wang et al ., ) used OsRac1 kd lines. We surmise that, in addition to its role in regulating immunity, OsRac1 is essential for rice growth and development and, therefore, that OsRac1 knockout mutants are lethal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, the presence of cofilins has been reported in various species (Hussey et al, 2002), while PP2A-2, an isoform of PP2A, is known to directly regulate ADF/cofilin (and, therefore, F-actin rearrangements) in Arabidopsis thaliana (Wen et al, 2012). In addition, OsRac1 (a rice homolog of Rac1), along with its activator GEF protein OsSPK1, have been recently suggested to be regulators of actin dynamics in rice (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that the LRR domain of ZAR1 plays an important role in interaction with the decoy RKS1, while also helping to maintain ZAR1 in an autoinhibition state through intramolecular interactions (Wang et al , 2019a). Both the CC and TIR domains have been shown to function as signalling components in plant NLRs (Swiderski et al , 2009; Bernoux et al , 2011; Baudin et al , 2017; Wang et al , 2018; Zhai et al , 2019). Indeed, the CC or TIR domains of numerous NLR proteins can trigger cell death when transiently expressed in Nicotiana benthamiana (Bernoux et al , 2011; Bai et al , 2012; Wang et al , 2015; Cesari et al , 2016; Hamel et al , 2016; Baudin et al , 2017; Kim et al , 2018).…”
Section: Introductionmentioning
confidence: 99%